2010
DOI: 10.1055/s-0029-1219166
|View full text |Cite
|
Sign up to set email alerts
|

Air-Stable Diaminophosphine Sulfides as Preligands for Nickel-Catalyzed Cross-Couplings of Unactivated Fluoro(hetero)arenes

Abstract: Air-stable secondary diaminophosphine sulfide preligands enable challenging nickel-catalyzed cross-coupling reactions of electron-deficient as well as electron-rich fluoro(hetero)arenes as electrophiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 5 publications
1
16
0
Order By: Relevance
“…Catalytic cross-coupling reactions of 2,3,5,6-tetrafluoropyridine. [4,14,17,21,[23][24][25][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]51,70]. Chambers and Sandford described palladium catalysed Suzuki cross-coupling reactions via C-Br activation of 2,4,6-tribromo-3,5-difluoropyridine and aromatic boronic acids.…”
Section: Bondmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalytic cross-coupling reactions of 2,3,5,6-tetrafluoropyridine. [4,14,17,21,[23][24][25][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]51,70]. Chambers and Sandford described palladium catalysed Suzuki cross-coupling reactions via C-Br activation of 2,4,6-tribromo-3,5-difluoropyridine and aromatic boronic acids.…”
Section: Bondmentioning
confidence: 99%
“…Thus, hydrodefluorination or cross coupling reactions can provide fluorinated building blocks, which are often not accessible otherwise . However, catalytic C-F bond functionalization reactions of highly fluorinated aromatic precursors via cross coupling reactions are still rare [4,14,17,[23][24][25][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. Radius et al reported an initial and exceptional example of a nickelmediated Suzuki-Miyaura cross coupling reaction of perfluorotoluene with aryl boronic acids on using a nickel(II) carbene complex as catalyst [25].…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal-catalysed Ar-F functionalization is considerably more challenging than classical Ar-H or Ar-Hal (Hal = I, Br, Cl) activation, generally showing low selectivities and requiring electronically biased polyfluorinated substrates. [5][6][7] In particular, C-C formation reaction via C-F cleavage of fluoroarenes using nickel catalyst has been reported for Kumada-Corriu, [8][9][10][11][12][13][14][15][16] Suzuki-Miyaura [17][18][19][20][21][22] and Negishi 23 cross-coupling reactions. However, all these methods use activated aryl nucleophiles, such as highly reactive Grignard reagents, zincates and boronic acids as the coupling partner for C-C formation via transmetallation (Scheme 1a).…”
mentioning
confidence: 99%
“…61) [114]. The reaction proceeded at ambient temperatures and produced monosubstituted products exclusively.…”
Section: ð59þmentioning
confidence: 99%